Oxime as a general photocage for the design of visible light photo-activatable fluorophores. Issue 47 (26th November 2021) - Wang, Lushun; Wang, Shichao; Tang, Juan; Espinoza, Vanessa B.; Loredo, Axel; Tian, Zeru; Weisman, R. Bruce; Xiao, Han
Abstract : Photoactivatable fluorophores have been widely used for tracking molecular and cellular dynamics with subdiffraction resolution. Abstract : Photoactivatable fluorophores have been widely used for tracking molecular and cellular dynamics with subdiffraction resolution. In this work, we have prepared a series of photoactivatable probes using the oxime moiety as a new class of photolabile caging group in which the photoactivation process is mediated by a highly efficient photodeoximation reaction. Incorporation of the oxime caging group into fluorophores results in loss of fluorescence. Upon light irradiation in the presence of air, the oxime-caged fluorophores are oxidized to their carbonyl derivatives, restoring strong fluorophore fluorescence. To demonstrate the utility of these oxime-caged fluorophores, we have created probes that target different organelles for live-cell confocal imaging. We also carried out photoactivated localization microscopy (PALM) imaging under physiological conditions using low-power light activation in the absence of cytotoxic additives. Our studies show that oximes represent a new class of visible-light photocages that can be widely used for cellular imaging, sensing, and photo-controlled molecular release.